A Rare Cause of Colonic Obstruction "Colonic Intussusception": Report of Two Cases. (10th March 2015) - Yoldas, Tayfun; Karaca, Avni Can; Ozturk, Safak; Unver, Mutlu; Calıskan, Cemil; Korkut, Mustafa Ali
Abstract : Colocolic intussusceptions are rare clinical entities in adults and almost always caused by a leading lesion which often warrants resection. Mostly being malignant, the leading lesions are rarely benign lesions where intraluminal lipomas are the most frequent among them. Most adult intussusceptions require surgical resection owing to two major reasons: common presence of a leading lesion and significantly high risk of malignancy—reaching as high as 65% regardless of the anatomic site—of the leading lesion. Resection of the affected segment is usually the treatment of choice, since preoperative diagnosis of the lesion is usually ineffective and most leading lesions are malignant. This paper represents two cases of adult colocolic intussusception caused by intraluminal lipomas with a brief review of the literature.